TOLERANCE AND SOCIAL CARE IN ISLAMIC PERSPECTIVE: A LITERATURE REVIEW - Mastur Thoyib (PT. Intelek Cendikiawan Nusantara, 2024)
As the Prophet's followers, we must, of course, adopt the type of tolerance demonstrated by him and his companions, the Khulafaur Rasyidin, who were also leaders of the Muslim community at the time. What they do is also an expression of Islam. Of course, as Muslims, we must learn from and emulate their example. We must also put Allah's message in the Koran into reality. As previously said, differences exist to complement, not mock, one other. However, the distinctions are not to be confounded. Humans can sustain peace simply by exhibiting mutual respect. Using literature review approach, this research highlights some relevant review on related literatures and shows that every Muslim has responsibility to enhance society and contribute to the development of social services within Muslim communities. Islam requires Muslims to aid others in whatever way and to the extent that their means allow. The importance of service to mankind, pushed its adherents to carry it out, and listed the people to be served. It has been argued that because all Muslims are members of the same community, they have a responsibility to aid one another in good and difficult times. They should never forget that it is their obligation to ensure everyone's well-being. They have a responsibility to never harbor any form of bias toward someone. It is demanded that every Muslim understand the close relation between tolerance and sosial care.